2011
DOI: 10.1242/jeb.048090
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in jaw-muscle architecture facilitate durophagy in the turtleSternotherus minor

Abstract: There was an error published in the original online version of J. Exp. Biol. 214, 1655-1667. This error occurred in both the PDF and fulltext versions of the online article. The print version is correct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Therefore, it is not surprising that a central focus of functional morphology studies is to understand how the scaling of the musculoskeletal system influences the scaling of functional traits across ontogeny. Previous studies have argued that ontogenetic shifts in ecology often drive adaptive changes in the scaling of musculoskeletal systems, resulting in differential performance (McMahon, 1984;Richard and Wainwright, 1995;Deban and O'Reilly, 2005;Herrel and Gibb, 2006;Pfaller et al, 2011). These studies, in turn, support the idea that allometric changes in morphology often co-occur with changes in feeding strategies, locomotor behavior or habitat use.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, it is not surprising that a central focus of functional morphology studies is to understand how the scaling of the musculoskeletal system influences the scaling of functional traits across ontogeny. Previous studies have argued that ontogenetic shifts in ecology often drive adaptive changes in the scaling of musculoskeletal systems, resulting in differential performance (McMahon, 1984;Richard and Wainwright, 1995;Deban and O'Reilly, 2005;Herrel and Gibb, 2006;Pfaller et al, 2011). These studies, in turn, support the idea that allometric changes in morphology often co-occur with changes in feeding strategies, locomotor behavior or habitat use.…”
Section: Introductionmentioning
confidence: 75%
“…geometry (Hill, 1950;Schmidt-Nielson, 1984;Emerson and Bramble, 1993;Pfaller et al, 2011). We considered deviations from isometry to be significant if the predicted slopes fell outside the 95% confidence intervals of the slopes we observed.…”
Section: Allometry Of Traitsmentioning
confidence: 99%
“…There is little ambiguity in deciding whether a prey item has been crushed, so there is a clear relationship between morphology and performance. The main determinant of predator success is the ability to exert high loads (Pfaller et al, 2011). For this reason it is possible to explore the implications of different predator and prey morphologies and to determine their interactions (Bertness and Cunningham, 1981;Whitenack and Herbert, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These authors were able to identify a high correlation with the increasing of muscle mass and shift in feeding features (Dalrymple, 1977; Pfaller et al, 2010; Pfaller, Gignac & Erickson, 2011). Moreover, there are changes in skull shape associated to the aquatic environment and foraging strategies, as suggested for emydid and testudinoid turtles by Claude et al (2004).…”
Section: Discussionmentioning
confidence: 97%
“…The variation in this area of the skull in turtles was a matter of some studies (e.g., Dalrymple, 1977; Claude et al, 2004; Pfaller, Gignac & Erickson, 2011), which indicated allometric ontogenetic growth patterns of the bones in these regions. These authors were able to identify a high correlation with the increasing of muscle mass and shift in feeding features (Dalrymple, 1977; Pfaller et al, 2010; Pfaller, Gignac & Erickson, 2011).…”
Section: Discussionmentioning
confidence: 97%